A systematic quantitative literature review of aquaculture genetic resource access and benefit sharing - Fran Humphries; John A.H. Benzie; Clare Morrison (Wiley Publishing Asia Pty Ltd, 2025)
The Convention on Biological Diversity provides a framework for countries to implement laws regulating the access, use and exchange of genetic resources, including how users and providers share the benefits from their use. While the international community has been preoccupied with resolving the unintended effects of access and benefit sharing (ABS) on domestication in agriculture for the past 25 years, its far-reaching consequences for global aquaculture has only recently dawned on policymakers, aquaculture producers and researchers. Using a systematic quantitative literature review methodology, we analysed the trends, biases and gaps in the ABS literature. Only 5% of the ABS literature related to the use and exchange of aquaculture genetic resources. Most of this literature related to use in developing countries or global use, but its authors were predominantly from developed countries. The literature covered a narrow range of countries (7) and regions (3), a narrow range of taxonomic groups (9) and a narrow range of uses. Given that aquaculture is the fastest growing global food production sector with products primarily from developing countries using over 580 species, there are significant gaps in aquaculture-related ABS literature. We conclude that the sector needs urgent analyses on the consequences of ABS restrictions, obligations and opportunities for its early stages of domestication and product development. We recommend priority areas for attention to ensure that rapidly evolving national ABS laws take into account the special characteristics and needs of the aquaculture sector.